Synthesis and fluorescence properties of selected phenoxy derivatives of pyrimidines and pyrazines / Shah Bakhtiar Nasir - Nasir, Shah Bakhtiar (2011)

(untitled)
2-(2-Methoxyphenoxy)pyrimidine (37), 2-(4-methoxyphenoxy)pyrimidine (39), 2-phenoxypyrimidine (41), 2-(3-methoxyphenoxy)pyrimidine (43), 2-(o-tolyloxy)pyrimidine (45), 2-(pyrimidin-2-yloxy)phenol (47), 2-(3-nitrophenoxy)pyrimidine (49) and 2-(p-tolyloxy)pyrimidine (51) were prepared by reacting 2-chloropyrimidine (35) with o-methoxyphenol, p-methoxyphenol, phenol, m-methoxyphenol, o-cresol, 1,2-dihydroxybenzene, m-nitrophenol and p-cresol respectively. Reactions of 2-chloropyrimidin-4-amine (52) with phenol produced 2-phenoxypyrimidin-4-amine (53), while reactions of 2-chloropyrazine (54) with o-methoxyphenol and p-methoxyphenol yielded 2-(2-methoxyphenoxy)pyrazine (55) and 2-(4-methoxyphenoxy)pyrazine (56) respectively. The structures of these compounds were confirmed using 1H NMR, 13C NMR, IR and GC-MS spectra. The fluorescence properties were recorded using Luminescence Spectrophotometer. All phenoxypyrimidines and phenoxypyrazines showed fluorescence properties in various solvents. Phenoxypyrimidines showed higher fluorescence intensity than phenoxypyrazines.